THE EFFECT OF PRICE AND QUALITY OF OIL PALM FRUIT ON THE INTEREST AND PURCHASE OF OIL PALM FRUIT AT RAM SAWIT IN CV PADANG MATINGGI VILLAGE, SIMUNDOL, SIMPANG AEK KANAN - Romadon, Deni; Muda Sipayung, Iskandar; Asriani Levianti, Rina (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
Abstract. This study aims to analyze the effect of price and quality of oil palm fruit on the interest and decision to buy and sell oil palm fruit to traders at CV Padang Matinggi Village, Simundol, Simpang Aek Kanan. Data were collected through questionnaires distributed to 35 farmers and palm oil traders. The results of multiple linear regression analysis show that the price and quality of oil palm fruits have a significant influence on transaction decisions with an R² of 0.939 which indicates that this regression model is able to explain 93.9% of the variation in transaction decisions. Among the two variables, palm fruit quality has a greater influence than selling interest with a regression coefficient of 6.065 for quality, while selling interest has an effect of 3.783 units. Although the effect of selling interest is smaller, both significantly influence the sale and purchase of oil palm fruits. This study shows that good fruit quality gives farmers a stronger bargaining position in the market and stable prices can increase the frequency of transactions. The practical implication of this study is the importance of optimal palm fruit quality management and fair and stable pricing to create an efficient and profitable market for all parties both farmers and traders.